Samak the Ayyar : a tale of ancient Persia - Mechner, Jordan (Columbia University Press, 2021)
"The adventures of Samak, a trickster-warrior hero of Persia's thousand-year-old oral storytelling tradition, are beloved in Iran. Samak is an ayyar, a warrior who comes from the common people and embodies the ideals of loyalty, selflessness, and honor-a figure that recalls samurai, ronin, and knights yet is distinctive to Persian legend. His exploits-set against an epic background of palace intrigue, battlefield heroics, and star-crossed romance between a noble prince and princess-are as deeply rooted in Persian culture as are the stories of Robin Hood and King Arthur in the West. However, this majestic tale has remained little known outside Iran. Translated from the original Persian by Freydoon Rassouli and adapted by Prince of Persia creator Jordan Mechner, this timeless masterwork can now be enjoyed by English-speaking readers. A thrilling and suspenseful saga, Samak the Ayyar also offers a vivid portrait of Persia a thousand years ago. Within an epic quest narrative teeming with action and supernatural forces, it sheds light on the lives of ordinary people and their social worlds. This is the first complete English-language version of a treasure of world culture. The translation is grounded in the twelfth-century Persian text while paying homage to the dynamic culture of storytelling from which it arose"--